The diversity, mite communities, and host specificity of pygmephoroid mites (Acari: Pygmephoroidea) associated with ants in Western Siberia, Russia - Khaustov, A. A.; Tolstikov, A. V. (Acarina, 2016)
This work discusses the diversity of mite communities along with host and attachment site specificities of myrmecophilous pygmephoroid mites (Acari: Pygmephoroidea) associated with most abundant ants (Hymenoptera: Formicidae) of Western Siberia. The researchers provide keys to myrmecophilous pygmephoroid mites of the families Neopygmephoridae and Scutacaridae of the Palaearctic and the keys to world species of the genera Caesarodispus Mahunka, 1977, and Unguidispus Mahunka, 1977 (Microdispidae). Petalomium aggtelekiensis Mahunka, 1977 and P. simplisetum Mahunka, 1986 are synonymized to P. chmelnickensis (Sevastianov, 1969), and P. carelitschensis (Sevastianov, 1967), respectively.